Swipe right for Mr. Perfect - Lewis, Justine (Harlequin romance, 2024)
"For art conservationist Laura, suffering chronic endometriosis means no relationships. Only, thanks to her interfering mother, she's matched online with @FarmerDan and can't bring herself to swipe left... But then she learns "Dan" is really her new boss, Henry, and their attraction is as intense in person as in cyberspace! Being a modern-day duke, Henry's duty-bound to produce an heir. So while meeting Laura is thrilling, it becomes clear that her condition makes her fertility uncertain. With life pulling them in different directions, is their connection strong enough to flourish offline?"--